Carbon carrier and preparation method thereof, catalyst and membrane electrode

By using a carbon support composed of unsealed carbon tubes and hollow carbon spheres, a catalyst with high porosity was prepared, which solved the problem of large mass transfer polarization loss of the membrane electrode catalytic layer and improved the power generation performance.

CN117810474BActive Publication Date: 2025-03-25SUZHOU HYDROGINE POWER TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311788631.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-25
Publication Date
2025-03-25
Estimated Expiration
2043-12-25

AI Technical Summary

Technical Problem

The mass transfer polarization loss of the catalytic layer in the existing membrane electrodes is large, resulting in poor transmission performance and affecting the power generation performance.

Method used

A carbon support with non-closed carbon tubes and non-closed hollow carbon balls connected to the outer surface of the carbon tube is used to prepare a catalyst through the carbonization treatment and acid liquid removal steps to improve the porosity and specific surface area of ​​the catalyst layer.

Benefits of technology

The porosity of the catalytic layer in the membrane electrode is improved, the mass transfer polarization loss and mass transfer resistance are reduced, and the power generation performance under high current density is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117810474B_ABST
    Figure CN117810474B_ABST
Patent Text Reader

Abstract

The present application provides a carbon carrier and a preparation method thereof, a catalyst and a membrane electrode, which belong to the field of fuel cell technology. The carbon carrier includes a carbon tube and a carbon sphere connected to the outer surface of the carbon tube; wherein the carbon sphere is a hollow structure, and both the carbon tube and the carbon sphere are non-closed structures. The carbon carrier provided in the present application has a porous structure and a large specific surface area. When the carbon carrier is used to prepare a catalyst, the carbon carriers are not easy to agglomerate, so that the prepared catalyst has a higher porosity, and the catalysts in the catalyst layer have larger pores, thereby increasing the porosity of the catalyst layer in the membrane electrode, which is beneficial to improving the transmission of the reactants in the catalyst layer, reducing the mass transfer polarization loss of the catalyst layer, and reducing the mass transfer resistance of the catalyst layer, thereby helping to improve the power generation performance of the membrane electrode at high current density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of fuel cell technology, and in particular to a carbon carrier and a preparation method thereof, a catalyst and a membrane electrode. Background Art

[0002] Fuel cells have the advantages of large capacity, small size and good safety, so they have certain advantages in mobile power products. The membrane electrode is the key core component of fuel cell power generation. The membrane electrode has a proton exchange membrane and a cathode catalyst layer and an anode catalyst layer located on opposite sides of the proton exchange membrane; the catalyst layer contains a catalyst, and the performance of the catalyst will affect the transmission performance of the membrane electrode, and thus affect the final power generation performance of the membrane electrode.

[0003] However, the mass transfer polarization loss of the catalytic layer in the membrane electrode is currently large, resulting in poor transport performance of the membrane electrode, which is not conducive to improving the power generation performance of the membrane electrode. Summary of the invention

[0004] The purpose of the present application is to provide a carbon carrier and a preparation method thereof, a catalyst and a membrane electrode, which are intended to improve the technical problem of large mass transfer polarization loss in the catalytic layer of the existing membrane electrode.

[0005] In a first aspect, the present application provides a carbon carrier, which includes a carbon tube and a carbon sphere connected to the outer surface of the carbon tube; wherein the carbon sphere is a hollow structure, and both the carbon tube and the carbon sphere are an open structure.

[0006] The carbon carrier provided in the present application has unclosed carbon tubes and unclosed hollow carbon spheres connected to the outer surface of the carbon tubes, which can make the carbon carrier have a pore structure and a large specific surface area. When the carbon carrier is used to prepare a catalyst, the carbon carriers are not easy to agglomerate, and the prepared catalyst has a high porosity. The catalysts in the catalytic layer have larger pores, which can increase the porosity of the catalytic layer in the membrane electrode, which is beneficial to improve the transmission of the reactants in the catalytic layer, reduce the mass transfer polarization loss of the catalytic layer, and reduce the mass transfer resistance of the catalytic layer, which is beneficial to improve the power generation performance of the membrane electrode under high current density.

[0007] In combination with the first aspect, in an optional embodiment of the present application, the length of the carbon tube is 60nm to 540nm, the outer diameter of the carbon tube is 30nm to 280nm, and the thickness of the carbon tube is 5nm to 20nm.

[0008] In the above technical solution, the size of the carbon tubes is within the above-mentioned limited range, which can make the size of the pore structure of the carbon carrier more appropriate, which is beneficial to further increase the specific surface area of ​​the carbon carrier and the porosity of the catalyst layer, and further help to further reduce the mass transfer resistance of the catalyst layer.

[0009] In combination with the first aspect, in an optional embodiment of the present application, the aspect ratio of the carbon tube is 2-12.

[0010] In the above technical solution, the aspect ratio of the carbon tube is within the above range, which is beneficial to further increase the specific surface area of ​​the carbon carrier, and further beneficial to further reduce the mass transfer resistance of the catalyst layer.

[0011] In combination with the first aspect, in an optional embodiment of the present application, the particle size of the carbon spheres is 15 nm to 60 nm, and the thickness of the carbon spheres is 5 nm to 20 nm.

[0012] In the above technical solution, the specific surface area of ​​the entire carbon carrier can be within a relatively suitable range, the porosity of the catalyst layer can be within a relatively suitable range, and thus the mass transfer resistance of the catalyst layer can be relatively low.

[0013] In combination with the first aspect, in an optional embodiment of the present application, the tube wall of the carbon tube and the spherical shell of the carbon sphere are both porous structures.

[0014] In the above technical solution, the tube wall of the carbon tube and the spherical shell of the carbon sphere are both porous structures. When the carbon carrier is used to prepare the catalyst, the catalytic material can be more evenly and fully dispersed on the outer surface of the carbon carrier, which is beneficial to improve the catalytic effect of the catalyst.

[0015] In a second aspect, the present application provides a method for preparing a carbon carrier, which comprises: performing a first mixing of a first liquid phase containing a rod-shaped metal oxide and a first carbon source to allow the first carbon source to undergo a polymerization reaction, and obtaining a first matrix after drying the solid phase; then performing a second mixing of a second liquid phase containing a spherical metal oxide and the first matrix, and obtaining a second matrix after drying the solid phase; then performing a third mixing of a third liquid phase containing a second carbon source and the second matrix to allow the second carbon source to undergo a polymerization reaction, and obtaining a third matrix after drying the solid phase; carbonizing the third matrix, and then performing a fourth mixing of the carbonized third matrix with an acid solution, so that the acid solution can remove the rod-shaped metal oxide and the spherical metal oxide in the third matrix.

[0016] By adopting the preparation method of the carbon carrier provided in the present application, the carbonization treatment can make the carbon source wrapped outside the rod-shaped metal oxide and the spherical metal oxide in the third matrix form a porous structure, so that the acid solution can contact with the rod-shaped metal oxide and the spherical metal oxide in the porous structure, and remove the rod-shaped metal oxide and the spherical metal oxide, so as to prepare a carbon carrier having unclosed carbon tubes and unclosed hollow carbon spheres connected to the outer surface of the carbon tubes; the prepared carbon carrier has a pore structure and a large specific surface area. When the carbon carrier is used to prepare a catalyst, the carbon carriers are not easy to agglomerate, so that the prepared catalyst has a higher porosity, and the catalysts in the catalyst layer have larger pores, so as to improve the porosity of the catalyst layer in the membrane electrode, which is beneficial to improve the transmission of the reactants in the catalyst layer, reduce the mass transfer polarization loss of the catalyst layer, and reduce the mass transfer resistance of the catalyst layer, so as to improve the power generation performance of the membrane electrode at high current density.

[0017] In combination with the second aspect, in an optional embodiment of the present application, the first carbon source and the second carbon source each independently include at least one of dopamine, pyrrole and aniline; or / and, the diameter of the rod-shaped metal oxide is 20nm to 240nm, and the length of the rod-shaped metal oxide is 50nm to 500nm; or / and, the aspect ratio of the rod-shaped metal oxide is 2.25-11.25; or / and, the mass ratio of the first carbon source to the rod-shaped metal oxide is 1:(5-20); or / and, the spherical The particle size of the spherical metal oxide is 10nm~50nm; or / and, the mass ratio of the spherical metal oxide to the first matrix is ​​1:(1~10); or / and, the materials of the spherical metal oxide and the rod-shaped metal oxide each independently include at least one of zinc oxide, copper oxide and magnesium oxide; or / and, the mass ratio of the second carbon source to the second matrix is ​​1:(0.25~4); or / and, the carbonization treatment is carried out under an inert atmosphere, and the temperature of the carbonization treatment is 800℃~1200℃.

[0018] In a third aspect, the present application provides a catalyst comprising a carbon carrier and a catalytic material loaded on the surface of the carbon carrier; wherein the carbon carrier is the carbon carrier provided in any one of the first aspects above, or the carbon carrier is a carbon carrier prepared by the preparation method of the carbon carrier provided in the second aspect above.

[0019] The catalyst provided in the present application, because it has the carbon carrier provided in the first aspect above or the carbon carrier prepared by the method for preparing the carbon carrier provided in the second aspect above, can make the catalytic layer containing the catalyst in the membrane electrode have a higher porosity, which is beneficial to improving the transmission of the reactants in the catalytic layer, reducing the mass transfer polarization loss of the catalytic layer, and reducing the mass transfer resistance of the catalytic layer, thereby helping to improve the power generation performance of the membrane electrode under high current density.

[0020] In combination with the third aspect, in an optional embodiment of the present application, the catalytic material includes at least one of Pt single substance and Pt alloy.

[0021] In a fourth aspect, the present application provides a membrane electrode, wherein the catalyst layer of the membrane electrode contains the catalyst provided in any one of the third aspects above.

[0022] The membrane electrode provided in the present application has good transmission performance and good power generation performance under high current density. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0024] Figure 1 This is a flow chart of the preparation process of the carbon carrier provided in this application.

[0025] Figure 2 The polarization curve diagram of the membrane electrode prepared using the catalyst prepared in Examples 1 to 3 of the present application.

[0026] Figure 3 The polarization curve diagram of the membrane electrode prepared using the catalysts prepared in Example 1 and Comparative Examples 1-2 of the present application. DETAILED DESCRIPTION

[0027] The present application provides a carbon carrier, which includes a carbon tube and a carbon ball connected to the outer surface of the carbon tube; wherein the carbon ball is a hollow structure, and both the carbon tube and the carbon ball are unclosed structures.

[0028] In the present application, "the carbon tube is an open structure" means: a carbon material having a hollow columnar structure and having holes or openings on the surface. It can be understood that the structure of the carbon tube does not necessarily refer to a standard round tube or square tube structure, but can also be a hollow columnar structure similar to a round tube or square tube. The present application does not limit the position of the holes or openings on the surface of the carbon tube. For example, the holes or openings on the surface of the carbon tube can be located at the end of the length direction of the carbon tube, or can be located on the surface of the carbon tube in the length direction; "the carbon ball has a hollow structure, and the carbon balls are all open structures" means: a carbon material having a hollow structure inside, a spherical or spherical shape, and having holes or openings on the surface. The present application does not limit the position of the holes or openings on the surface of the carbon ball. For example, the holes or openings on the surface of the carbon ball can be located at any position on the surface of the carbon ball.

[0029] The carbon carrier provided in the present application has unclosed carbon tubes and unclosed hollow carbon spheres connected to the outer surface of the carbon tubes, which can make the carbon carrier have a pore structure and a large specific surface area. When the carbon carrier is used to prepare a catalyst, the carbon carriers are not easy to agglomerate, so that the prepared catalyst has a higher porosity, and the catalysts in the catalyst layer have larger pores, which can increase the porosity of the catalyst layer in the membrane electrode, which is beneficial to improve the transmission of the reaction substances in the catalyst layer, reduce the mass transfer polarization loss of the catalyst layer, reduce the mass transfer resistance of the catalyst layer, and increase the three-phase reaction active area of ​​the catalyst, which is beneficial to improve the power generation performance of the membrane electrode under high current density.

[0030] In some optional embodiments of the present application, the length of the carbon tube is 60 nm to 540 nm, the outer diameter of the carbon tube is 30 nm to 280 nm, and the thickness of the carbon tube is 5 nm to 20 nm.

[0031] In the present application, the thickness of a carbon tube refers to the difference between the outer diameter and the inner diameter at the same point on the carbon tube.

[0032] The size of the carbon tubes being within the above-defined range can make the size of the pore structure of the carbon carrier more appropriate, which is beneficial to further increase the specific surface area of ​​the carbon carrier and the porosity of the catalyst layer, thereby further reducing the mass transfer resistance of the catalyst layer.

[0033] As an example, the length of the carbon tube can be any value among 60nm, 80nm, 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, 500nm and 540nm, or a range value between any two of them; the outer diameter of the carbon tube can be any value among 30nm, 50nm, 80nm, 100nm, 120nm, 150nm, 175nm, 200nm, 240nm, 260nm and 280nm, or a range value between any two of them; the thickness of the carbon tube can be any value among 5nm, 7nm, 9nm, 10nm, 12nm, 15nm, 17nm and 20nm, or a range value between any two of them.

[0034] Furthermore, in some optional embodiments of the present application, the aspect ratio of the carbon tube is 2-12.

[0035] In the present application, the aspect ratio of a carbon tube refers to the ratio of the length dimension to the outer diameter dimension of the carbon tube.

[0036] The aspect ratio of the carbon tube is 2 to 12, which is beneficial to further increase the specific surface area of ​​the carbon carrier, and further beneficial to further reduce the mass transfer resistance of the catalyst layer.

[0037] As an example, the aspect ratio of the carbon tube can be any value among 2, 3, 4, 5, 6, 7, 8, 9, 10, 11 and 12, or a range value between any two of them.

[0038] In some optional embodiments of the present application, the particle size of the carbon balls is 15nm to 60nm, and the thickness of the carbon balls is 5nm to 20nm; the specific surface area of ​​the entire carbon carrier can be within a more appropriate range, and the porosity of the catalytic layer can be within a more appropriate range, thereby making the mass transfer resistance of the catalytic layer lower; if the particle size of the carbon balls is larger, the porosity of the catalytic layer may be slightly reduced; if the particle size of the carbon balls is smaller, some carbon balls may agglomerate, resulting in a reduction in the specific surface area of ​​the carbon carrier.

[0039] In the present application, the thickness of a carbon sphere refers to the difference between the outer diameter and the inner diameter at the same point on the carbon sphere along the radial direction of the carbon sphere.

[0040] As an example, the particle size of the carbon sphere can be any value among 15nm, 20nm, 25nm, 30nm, 35nm, 40nm, 45nm, 50nm, 55nm and 60nm, or a range value between any two of them; the thickness of the carbon sphere can be any value among 5nm, 7nm, 9nm, 10nm, 12nm, 15nm, 17nm and 20nm, or a range value between any two of them.

[0041] Furthermore, in some optional embodiments of the present application, the particle size of the carbon spheres is 20 nm to 40 nm, which is beneficial for further reducing the mass transfer resistance of the catalytic layer.

[0042] In some optional embodiments of the present application, the tube wall of the carbon tube and the spherical shell of the carbon sphere are both porous structures; when the carbon carrier is used to prepare the catalyst, the catalytic material can be more evenly and fully dispersed on the outer surface of the carbon carrier, which is beneficial to improving the catalytic effect of the catalyst.

[0043] In the present application, the porous structure of the carbon tube wall means that: the surface of the hollow carbon tube has multiple holes, and the interior of the carbon tube is not a hollow structure to form a porous structure; the spherical shell of the carbon sphere: the surface of the hollow carbon sphere has multiple holes, and the interior of the carbon sphere is not a hollow structure to form a porous structure.

[0044] The present application provides a method for preparing a carbon carrier, which comprises: performing a first mixing of a first liquid phase containing a rod-shaped metal oxide and a first carbon source so as to allow the first carbon source to undergo a polymerization reaction, and obtaining a first matrix after drying the solid phase; then performing a second mixing of a second liquid phase containing a spherical metal oxide and the first matrix, and obtaining a second matrix after drying the solid phase; then performing a third mixing of a third liquid phase containing a second carbon source and the second matrix so as to allow the second carbon source to undergo a polymerization reaction, and obtaining a third matrix after drying the solid phase; carbonizing the third matrix, and then performing a fourth mixing of the carbonized third matrix with an acid solution so as to allow the acid solution to remove the rod-shaped metal oxide and the spherical metal oxide in the third matrix.

[0045] By adopting the preparation method of the carbon carrier provided above, the carbonization treatment can form a porous structure of the carbon source wrapped by the rod-shaped metal oxide and the spherical metal oxide in the third matrix, so that the acid solution can contact the rod-shaped metal oxide and the spherical metal oxide in the porous structure, and remove the rod-shaped metal oxide and the spherical metal oxide, so as to prepare a carbon carrier having an unclosed carbon tube and an unclosed hollow carbon sphere connected to the outer surface of the carbon tube; the prepared carbon carrier has a pore structure and a large specific surface area. When the carbon carrier is used to prepare a catalyst, the carbon carriers are not easy to agglomerate, so that the prepared catalyst has a high porosity, and the catalysts in the catalyst layer have large pores, so as to improve the porosity of the catalyst layer in the membrane electrode, which is beneficial to improve the transmission of the reaction substances in the catalyst layer, reduce the mass transfer polarization loss of the catalyst layer, and reduce the mass transfer resistance of the catalyst layer, so as to improve the power generation performance of the membrane electrode at high current density. In addition, the preparation method of the carbon carrier provided in the present application is simple and easy to shape, and is suitable for industrial production.

[0046] Figure 1 For the preparation process flow chart of the carbon carrier provided in this application, please refer to Figure 1 , the preparation method of the carbon carrier comprises the following steps:

[0047] S10, performing a first mixing of a first liquid phase containing a rod-shaped metal oxide and a first carbon source to allow the first carbon source to undergo a polymerization reaction, and drying the solid phase to obtain a first matrix.

[0048] In the present application, the first carbon source undergoes a polymerization reaction in the first mixing process, the first carbon source is coated on the outer surface of the rod-shaped metal oxide, and the polymerization reaction can connect the first carbon sources to each other to form a preliminary tubular structure, so that the spherical metal oxide in step S20 can be more stably loaded on the outer surface of the first substrate, and the second carbon source in step S30 can be more stably loaded on the outer surface of the first substrate; it can be understood that in the present application, the first carbon source is a monomer containing carbon elements and can undergo polymerization reaction.

[0049] In some optional embodiments of the present application, the first carbon source is a carbon source that becomes a conductive polymer after polymerization; this can improve the electrode conductivity of the membrane electrode, reduce the electrode impedance, and increase the electrode activity, thereby improving the transmission performance of the membrane electrode.

[0050] In some optional embodiments of the present application, the first carbon source includes at least one of dopamine, pyrrole and aniline. The first carbon source is selected from the above substances, so that the first carbon source can be stably coated on the outer surface of the rod-shaped metal oxide to form a preliminary tubular structure. After the first carbon source is coated on the outer surface of the rod-shaped metal oxide, the first carbon source undergoes a polymerization reaction, so that the first carbon sources can be connected to each other, which can improve the structural strength of the tubular structure, and then a relatively stable hollow carbon tube is formed after the rod-shaped metal oxide is removed by acid solution.

[0051] It can be understood that, when the first carbon source is dopamine, there is no need to add an initiator to the first liquid phase to initiate the polymerization of dopamine, but the first liquid phase is adjusted to be alkaline to allow dopamine to undergo polymerization reaction; and when the first carbon source is pyrrole or aniline, an initiator needs to be added to the first liquid phase to initiate the polymerization reaction of pyrrole or aniline.

[0052] Furthermore, in some optional embodiments of the present application, the first carbon source is dopamine, and the catechol group and amino group in dopamine have adhesion properties, which can make the first carbon source adhere to the outer surface of the rod-shaped metal oxide more stably, and then form a hollow carbon tube with a relatively stable structure after the rod-shaped metal oxide is removed by acid solution.

[0053] When the first carbon source is dopamine, the first liquid phase is alkaline (eg, pH 8.0-9.0). As an example, a Tris-HCl buffer may be used to adjust the first liquid phase to be alkaline.

[0054] In the present application, the rod-shaped metal oxide refers to a metal oxide material that can react with an acid so that the rod-shaped metal oxide can be dissolved and converted into a liquid phase, and the metal oxide is a rod-shaped or rod-like long strip structure.

[0055] In some optional embodiments of the present application, the material of the rod-shaped metal oxide includes at least one of zinc oxide, copper oxide and magnesium oxide. It should be noted that the material of the rod-shaped metal oxide is not limited to the above substances, as long as it can react with acid and convert into a liquid phase.

[0056] In some optional embodiments of the present application, the diameter of the rod-shaped metal oxide is 20nm to 240nm, and the length of the rod-shaped metal oxide is 50nm to 500nm; this can make the length of the formed carbon tube more appropriate, and make the size of the pore structure of the carbon carrier more appropriate, which is beneficial to further increase the specific surface area of ​​the carbon carrier and the porosity of the catalytic layer, and further help to further reduce the mass transfer resistance of the catalytic layer.

[0057] As an example, the diameter of the rod-shaped metal oxide can be any value among 20nm, 50nm, 80nm, 100nm, 120nm, 150nm, 175nm, 200nm, 220nm and 240nm, or a range value between any two thereof; the length of the rod-shaped metal oxide can be any value among 50nm, 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm and 500nm, or a range value between any two thereof.

[0058] In some optional embodiments of the present application, the aspect ratio of the rod-shaped metal oxide is 2.25 to 11.25; this is beneficial to further increase the specific surface area of ​​the carbon carrier, and further to further reduce the mass transfer resistance of the catalytic layer.

[0059] As an example, the aspect ratio of the rod-shaped metal oxide can be any value among 2.25, 3, 3.25, 4, 4.25, 5, 5.25, 6, 6.25, 7, 7.25, 8, 8.25, 9, 9.25, 10, 10.25, 11 and 11.25, or any range therebetween.

[0060] In some optional embodiments of the present application, the mass ratio of the first carbon source to the rod-shaped metal oxide is 1:(5-20); the first carbon source can be more fully wrapped on the outer surface of the rod-shaped metal oxide, and the outer diameter and thickness of the formed carbon tube are more appropriate, which is beneficial to further increase the specific surface area of ​​the carbon carrier and the porosity of the catalytic layer, and further help to further reduce the mass transfer resistance of the catalytic layer.

[0061] As an example, the mass ratio of the first carbon source to the rod-shaped metal oxide may be any value among 1:5, 1:7, 1:9, 1:10, 1:12, 1:15, 1:17 and 1:20 or a range value between any two of them.

[0062] In some optional embodiments of the present application, the solvent in the first liquid phase is water.

[0063] In some optional embodiments of the present application, the first mixing is performed by mechanical stirring, and the first mixing time is 12h to 36h; this allows the first carbon source to be more stably and fully coated on the outer surface of the rod-shaped metal oxide, and the polymerization reaction of the first carbon source is more complete.

[0064] In some optional embodiments of the present application, the step of drying the solid phase includes: filtering and washing the first mixed solid phase with deionized water for 2 to 4 times, and then drying the solid phase using a vacuum drying method.

[0065] Furthermore, the temperature for drying the solid phase can be 60° C. to 80° C., and the time for drying the solid phase is not less than 8 hours.

[0066] S20, performing a second mixing on the second liquid phase containing the spherical metal oxide and the first matrix, and drying the solid phase to obtain a second matrix.

[0067] In the present application, the spherical metal oxide refers to a metal oxide material that can react with an acid so that the spherical metal oxide can be dissolved and converted into a liquid phase, and the metal oxide is a sphere or a spherical-like structure.

[0068] In the present application, during the second mixing process, the spherical metal oxides can be relatively stably loaded on the outer surface of the first substrate.

[0069] In some optional embodiments of the present application, the material of the spherical metal oxide includes at least one of zinc oxide, copper oxide and magnesium oxide. It should be noted that the material of the spherical metal oxide is not limited to the above substances, as long as it can react with acid and convert into liquid phase.

[0070] In some optional embodiments of the present application, the particle size of the spherical metal oxide is 10nm to 50nm; this allows the size of the hollow carbon spheres formed after the spherical metal oxides are removed by acid to be within a more suitable range, so that the porosity of the catalytic layer is within a more suitable range, thereby lowering the mass transfer resistance of the catalytic layer.

[0071] As an example, the particle size of the spherical metal oxide can be any value among 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm and 50 nm, or a range value between any two of them.

[0072] Furthermore, in some optional embodiments of the present application, the particle size of the spherical metal oxide is 20 nm to 40 nm; this is beneficial for further reducing the mass transfer resistance of the catalytic layer.

[0073] In some optional embodiments of the present application, the mass ratio of the spherical metal oxide to the first substrate is 1:(1-10); this not only allows the spherical metal oxide to be more fully loaded on the outer surface of the first substrate, but also helps to avoid agglomeration of the spherical metal oxides, so that the porosity of the catalytic layer is within a more appropriate range, thereby reducing the mass transfer resistance of the catalytic layer.

[0074] As an example, the mass ratio of the spherical metal oxide to the first matrix can be any value among 1:1, 3:5, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9 and 1:10, or a range value between any two of them.

[0075] Furthermore, in some optional embodiments of the present application, the mass ratio of the spherical metal oxide to the first substrate is 1:(3-7), which is beneficial to further reduce the mass transfer resistance of the catalytic layer.

[0076] In some optional embodiments of the present application, the solvent in the second liquid phase is water.

[0077] In some optional embodiments of the present application, the second mixing adopts ultrasonic mixing, which can make the spherical metal oxide be more stably loaded on the outer surface of the first substrate.

[0078] Furthermore, the ultrasonic power of the ultrasonic mixing is 80 Hz to 100 Hz, and the ultrasonic mixing time is not less than 12 hours. Still further, the ultrasonic mixing time is 12 hours to 24 hours.

[0079] In some optional embodiments of the present application, the step of drying the solid phase includes: filtering and washing the second mixed solid phase with deionized water for 2 to 4 times, and then drying the solid phase using a vacuum drying method.

[0080] Furthermore, the temperature for drying the solid phase can be 60° C. to 80° C., and the time for drying the solid phase is not less than 8 hours.

[0081] S30, performing a third mixing on the third liquid phase containing the second carbon source and the second matrix to polymerize the second carbon source, and drying the solid phase to obtain a third matrix.

[0082] In the present application, the second carbon source undergoes a polymerization reaction in the third mixing process, and the second carbon source is coated on the outer surface of the spherical metal oxide and the outer surface of the tubular structure formed by the outer surface of the rod-shaped metal oxide (i.e., the polymer after the first carbon source is polymerized), that is, the second carbon source can be relatively stably coated on the outer surface of the second substrate, and the polymerization reaction can connect the second carbon sources and the polymers after the second carbon source and the first carbon source are polymerized to each other to form a spherical / rod-like structure (i.e., the outer surface of the rod-like structure is loaded with the spherical structure); it can be understood that in the present application, the second carbon source is a monomer containing carbon elements and can undergo polymerization reactions.

[0083] In some optional embodiments of the present application, the second carbon source is a carbon source that is a conductive polymer after polymerization; this can improve the electrode conductivity of the membrane electrode, reduce the electrode impedance, and increase the electrode activity, thereby improving the transmission performance of the membrane electrode.

[0084] In some optional embodiments of the present application, the second carbon source includes at least one of dopamine, pyrrole and aniline. The second carbon source is selected from the above substances, so that the second carbon source can be stably coated on the outer surface of the tubular structure formed by the outer surface of the spherical metal oxide and the outer surface of the rod-shaped metal oxide (i.e., the polymer after the first carbon source is polymerized) to form a ball / rod-shaped structure. After the second carbon source is coated on the outer surface of the tubular structure formed by the outer surface of the spherical metal oxide and the rod-shaped metal oxide, the second carbon source undergoes a polymerization reaction, so that the second carbon sources and the polymers after the second carbon source and the first carbon source are connected to each other, which can improve the structural strength of the ball / rod-shaped structure, and then a relatively stable hollow carbon ball / rod structure (i.e., the outer surface of the hollow rod-shaped structure loads the hollow spherical structure) is formed after the acid solution removes the spherical metal oxide and the rod-shaped metal oxide.

[0085] It can be understood that when the second carbon source is dopamine, there is no need to add an initiator to the third liquid phase to initiate the polymerization of dopamine. Instead, the third liquid phase is adjusted to be alkaline to allow dopamine to undergo polymerization. When the third carbon source is pyrrole or aniline, an initiator needs to be added to the third liquid phase to initiate the polymerization reaction of pyrrole or aniline.

[0086] Furthermore, in some optional embodiments of the present application, the third carbon source is dopamine. The catechol group and amino group in dopamine have adhesion properties, which can make the third carbon source adhere more stably to the outer surface of the spherical metal oxide and the outer surface of the tubular structure formed by the outer surface of the rod-shaped metal oxide (i.e., the polymer after the first carbon source is polymerized), and then after the spherical and rod-shaped metal oxides are removed by acid solution, a relatively stable hollow carbon sphere / rod is formed, and the structural stability between the hollow carbon sphere and the hollow carbon tube is better.

[0087] When the second carbon source is dopamine, the third liquid phase is alkaline (eg, pH 8.0-9.0). As an example, a Tris-HCl buffer can be used to adjust the third liquid phase to be alkaline.

[0088] In some optional embodiments of the present application, the solvent in the third liquid phase is water.

[0089] In some optional embodiments of the present application, the mass ratio of the second carbon source to the second matrix is ​​1:(0.25-4); this can make the particle size and thickness of the hollow carbon spheres and hollow carbon tubes within a more appropriate range, and can make the entire carbon carrier have a higher specific surface area, which is beneficial to further reduce the mass transfer resistance of the catalytic layer.

[0090] As an example, the mass ratio of the second carbon source to the second matrix can be any value among 1:0.25, 1:0.5, 1:0.75, 1:1, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5 and 1:4, or a range value between any two of them.

[0091] In some optional embodiments of the present application, the third mixing is performed by mechanical stirring mixing, and the third mixing time is 12h to 36h; this allows the second carbon source to be more stably and fully coated on the outer surface of the spherical metal oxide and the outer surface of the tubular structure formed by the outer surface of the rod-shaped metal oxide, and the polymerization reaction of the second carbon source is more complete.

[0092] In some optional embodiments of the present application, the step of drying the solid phase includes: filtering and washing the third mixed solid phase with deionized water for 2 to 4 times, and then drying the solid phase using a vacuum drying method.

[0093] Furthermore, the temperature for drying the solid phase can be 60° C. to 80° C., and the time for drying the solid phase is not less than 8 hours.

[0094] S40, performing carbonization treatment on the third substrate.

[0095] In the present application, carbonization treatment refers to a process in which organic matter such as a product of polymerization of the first carbon source and the second carbon source in the third matrix is ​​converted into carbon.

[0096] In some optional embodiments of the present application, the carbonization treatment is performed under an inert atmosphere (eg, nitrogen or argon, etc.), and the temperature of the carbonization treatment is 800° C. to 1200° C., and the time of the carbonization treatment is 1 h to 3 h.

[0097] As an example, the temperature of the carbonization treatment can be any value among 800°C, 850°C, 900°C, 950°C, 1000°C, 1050°C, 1100°C, 1150°C and 1200°C, or a range between any two values.

[0098] In some optional embodiments of the present application, the step of carbonization treatment includes: replacing with an inert gas at a flow rate of 200mL / min to 300mL / min for 20min to 60min; heating to 800℃ to 1200℃ at a heating rate of 10℃ / min to 50℃ / min under an inert atmosphere, and then keeping warm for 1h to 3h.

[0099] S50, performing a fourth mixing of the carbonized third substrate and the acid solution, so that the acid solution can remove the rod-shaped metal oxides and the spherical metal oxides in the third substrate.

[0100] In the present application, the acid solution refers to an acid solution that can react with the rod-shaped metal oxide and the spherical metal oxide and convert the rod-shaped metal oxide and the spherical metal oxide into a liquid phase. As an example, the acid solution can be dilute hydrochloric acid, dilute sulfuric acid or dilute nitric acid.

[0101] In some optional embodiments of the present application, the concentration of the acid solution may be 0.5 mol / L to 1 mol / L.

[0102] In some optional embodiments of the present application, the temperature of the fourth mixing is 60° C. to 90° C., and the time of the fourth mixing is 3 h to 12 h.

[0103] The present application also provides a catalyst, which includes: a carbon carrier and a catalytic material loaded on the surface of the carbon carrier; wherein the carbon carrier is the carbon carrier provided above, or the carbon carrier is a carbon carrier prepared by the preparation method of the provided carbon carrier.

[0104] The catalyst provided in the present application can make the catalytic layer containing the catalyst in the membrane electrode have a higher porosity, which is beneficial to improving the transmission of the reactants in the catalytic layer, reducing the mass transfer polarization loss of the catalytic layer, and reducing the mass transfer resistance of the catalytic layer, thereby helping to improve the power generation performance of the membrane electrode under high current density.

[0105] In some optional embodiments of the present application, the catalytic material includes at least one of a Pt element and a Pt alloy. As an example, the Pt alloy can be selected from a PtCo alloy, a PtFe alloy, a PtCu alloy, a PtNi alloy, a PtMn alloy, a PtCr alloy, a PtPd alloy, a PtIr alloy, a PtAu alloy, a PtAg alloy or a PtRu alloy, etc.

[0106] It should be noted that the present application does not limit the catalytic material, as long as it has catalytic activity.

[0107] The present application provides a method for preparing the catalyst provided above, which comprises: mixing a liquid phase containing a carbon carrier and a catalytic material precursor, drying the solid phase to obtain an intermediate; and then treating the intermediate to convert the catalytic material precursor in the intermediate into a catalytic material.

[0108] In the present application, the catalytic material precursor refers to: a precursor containing the corresponding elements in the catalytic material, which can be converted into the catalytic material during the subsequent processing (ie, the processing of the intermediate).

[0109] In some optional embodiments of the present application, the liquid phase containing the carbon carrier and the catalyst material precursor is mixed by ultrasonic mixing; the ultrasonic mixing method can make the catalyst material precursor more fully loaded on the carbon carrier.

[0110] Furthermore, the ultrasonic power of the ultrasonic mixing is 80 Hz to 100 Hz, and the ultrasonic mixing time is not less than 2 hours. Still further, the ultrasonic mixing time is 2 hours to 5 hours.

[0111] As an example, when the catalytic material is a single substance of Pt, the catalytic material precursor may be chloroplatinic acid, and the preparation method of the catalyst includes: mixing a liquid phase containing a carbon carrier and chloroplatinic acid, drying a solid phase to obtain an intermediate; and then performing a thermal reduction treatment on the intermediate to convert the chloroplatinic acid into a single substance of Pt. Furthermore, the solvent in the liquid phase containing the carbon carrier and the catalytic material precursor is water.

[0112] Furthermore, the step of drying the solid phase to obtain the intermediate includes: transferring the solid phase to a carrier (e.g., a glass watch glass), rapidly prefreezing (e.g., prefreezing with liquid nitrogen or prefreezing in a low-temperature refrigerator), and then lyophilizing (e.g., a lyophilization rate of 5°C / min to 20°C / min).

[0113] As an example, the steps of thermal reduction treatment include: replacing with an inert gas for 20 minutes to 60 minutes, then introducing a mixture of hydrogen and nitrogen in a volume ratio of 1: (6 to 20), heating to 300°C to 700°C at a heating rate of 10°C / min to 50°C / min, and keeping warm for 1h to 3h; then introducing an inert gas (nitrogen or argon) for 1h to 2h, and allowing the heat-treated system to cool naturally to room temperature.

[0114] The present application also provides a membrane electrode, the catalyst layer of which contains the catalyst provided above.

[0115] The membrane electrode provided in the present application has good transmission performance and good power generation performance under high current density.

[0116] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0117] Example 1

[0118] This embodiment provides a catalyst, which is prepared by the following steps:

[0119] (1) 8 g of rod-shaped zinc oxide and 1 g of dopamine were dispersed and stirred in 900 mL of water, and then the pH of the system was adjusted to 8.5 with Tris-HCl buffer and stirred for 12 h; the solid phase was washed by filtration with deionized water for 3 times, and then the solid phase was placed in a vacuum oven at 80° C. and dried for 8 h to obtain a first matrix.

[0120] The average diameter of the rod-shaped zinc oxide is 80 nm, and the average length of the rod-shaped zinc oxide is 500 nm.

[0121] (2) 5 g of the first matrix prepared in step (1) and 1 g of spherical zinc oxide were ultrasonically mixed in 600 mL of water, the solid phase was filtered and washed three times with deionized water, and then the solid phase was placed in a vacuum oven at 80° C. and dried for 8 h to obtain a second matrix.

[0122] Wherein, the D50 of the spherical zinc oxide is 30 nm, the power of ultrasonic mixing is 90 Hz, and the time of ultrasonic mixing is 2 h.

[0123] (3) Disperse 2 g of the second matrix obtained in step (2) and 1 g of dopamine in 300 mL of water and stir, then adjust the system to pH = 8.5 with Tris-HCl buffer and stir for 12 h; use deionized water to filter and wash the solid phase three times, then place the solid phase in a vacuum oven at 80°C and dry for 8 h to obtain a third matrix.

[0124] (4) The third substrate prepared in step (3) is placed in a tubular furnace and replaced with N2 at a flow rate of 200 mL / min for 30 min; under N2, the temperature is increased to 900°C at a heating rate of 20°C / min, and kept at this temperature for 2 h. After the temperature is lowered to room temperature, the third substrate after carbonization treatment is obtained.

[0125] (5) The third substrate obtained in step (4) after carbonization treatment is immersed in a 0.5 mol / L dilute nitric acid solution and treated at 60°C for 6 hours. The solid phase is filtered and washed three times with deionized water, and then the solid phase is placed in a vacuum oven at 80°C and dried for 8 hours to obtain a carbon carrier.

[0126] (6) 0.60 g of the carbon carrier prepared in step (5) was ultrasonically mixed with 1.06 g of chloroplatinic acid in 6 mL of water, and then the system after ultrasonic mixing was transferred to a glass surface dish, quickly pre-frozen in liquid nitrogen, and then transferred to a freeze dryer, cooled to -20°C at a freeze drying rate of 10°C / min, and then kept for 10 hours. The freeze-dried system was then transferred to a porcelain boat and placed in a tube furnace, first replaced with N2 for 30 minutes, and then a mixed gas of H2 and N2 with a volume ratio of 0.075:1 was introduced, and the temperature was raised to 300°C at a heating rate of 20°C / min, and kept warm for 2 hours; then N2 was introduced for 1 hour, and then the temperature was reduced to room temperature to obtain a catalyst.

[0127] Example 2

[0128] This embodiment provides a catalyst. The only difference between this embodiment and embodiment 1 is that the D50 of the spherical zinc oxide is 50 nm.

[0129] Example 3

[0130] This embodiment provides a catalyst. The only difference between this embodiment and embodiment 1 is that the D50 of the spherical zinc oxide is 10 nm.

[0131] Example 4

[0132] This embodiment provides a catalyst. The only difference between this embodiment and embodiment 1 is that the average diameter of the rod-shaped zinc oxide is 200 nm, and the average length of the rod-shaped zinc oxide is 450 nm.

[0133] Example 5

[0134] This embodiment provides a catalyst. The only difference between this embodiment and embodiment 1 is that the average diameter of the rod-shaped zinc oxide is 45 nm, and the average length of the rod-shaped zinc oxide is 500 nm.

[0135] Example 6

[0136] This embodiment provides a catalyst. The only difference between this embodiment and embodiment 1 is that in step (1), the masses of the rod-shaped zinc oxide and dopamine are 5 g and 1 g, respectively.

[0137] Example 7

[0138] This embodiment provides a catalyst. The only difference between this embodiment and embodiment 1 is that in step (1), the masses of the rod-shaped zinc oxide and dopamine are 20 g and 1 g, respectively.

[0139] Example 8

[0140] This embodiment provides a catalyst. The only difference between this embodiment and embodiment 1 is that in step (2), the masses of the first substrate and the spherical zinc oxide are 1 g and 1 g respectively.

[0141] Example 9

[0142] This embodiment provides a catalyst. The only difference between this embodiment and embodiment 1 is that in step (2), the masses of the first substrate and the spherical zinc oxide are 10 g and 1 g, respectively.

[0143] Example 10

[0144] This embodiment provides a catalyst. The only difference between this embodiment and embodiment 1 is that in step (2), the masses of the first substrate and the spherical zinc oxide are 3 g and 1 g, respectively.

[0145] Embodiment 11

[0146] This embodiment provides a catalyst. The only difference between this embodiment and embodiment 1 is that in step (2), the masses of the first substrate and the spherical zinc oxide are 7 g and 1 g, respectively.

[0147] Example 12

[0148] This embodiment provides a catalyst. The only difference between this embodiment and embodiment 1 is that in step (2), the masses of the first substrate and the spherical zinc oxide are 5 g and 3 g, respectively.

[0149] Example 13

[0150] This embodiment provides a catalyst. The only difference between this embodiment and embodiment 1 is that in step (3), the masses of the second substrate and dopamine are 0.25 g and 1 g, respectively.

[0151] Embodiment 14

[0152] This embodiment provides a catalyst. The only difference between this embodiment and embodiment 1 is that in step (3), the masses of the second substrate and dopamine are 4 g and 1 g, respectively.

[0153] Embodiment 15

[0154] This embodiment provides a catalyst. The difference between this embodiment and embodiment 1 is only that steps (1) to (3) are different. In this embodiment, steps (1) to (3) are respectively as follows:

[0155] (1) 8 g of rod-shaped zinc oxide and 1 g of pyrrole were dispersed and stirred in 900 mL of water, and then 2 g of ferric chloride was added and stirred at 5° C. for 12 h; the solid phase was washed by filtration with deionized water for 3 times, and then the solid phase was placed in a vacuum oven at 80° C. and dried for 8 h to obtain a first matrix.

[0156] The average diameter of the rod-shaped zinc oxide is 80 nm, and the average length of the rod-shaped zinc oxide is 500 nm.

[0157] (2) 5 g of the first matrix prepared in step (1) and 1 g of spherical zinc oxide were ultrasonically mixed in 600 ml of water, the solid phase was filtered and washed three times with deionized water, and then the solid phase was placed in a vacuum oven at 80° C. and dried for 8 h to obtain a second matrix.

[0158] Wherein, the D50 of the spherical zinc oxide is 30 nm, the power of ultrasonic mixing is 90 Hz, and the time of ultrasonic mixing is 2 h.

[0159] (3) Disperse and stir 2 g of the second matrix obtained in step (2) and 1 g of pyrrole in 300 ml of water, then add 2 g of ferric chloride and stir at 5°C for 12 h; use deionized water to filter and wash the solid phase three times, then place the solid phase in a vacuum oven at 80°C and dry it for 8 h to obtain a third matrix.

[0160] Comparative Example 1

[0161] This comparative example provides a catalyst. The difference between this comparative example and Example 1 is that the preparation steps of the carbon carrier are different. In this comparative example, the preparation steps of the carbon carrier are as follows:

[0162] (1) 2 g of rod-shaped zinc oxide and 1 g of dopamine were dispersed and stirred in 300 mL of water, and then the pH of the system was adjusted to 8.5 with Tris-HCl buffer and stirred for 12 h; the solid phase was washed by filtration with deionized water for 3 times, and then the solid phase was placed in a vacuum oven at 80° C. and dried for 8 h to obtain a first matrix.

[0163] The average diameter of the rod-shaped zinc oxide is 80 nm, and the average length of the rod-shaped zinc oxide is 500 nm.

[0164] (2) The first substrate prepared in step (1) is placed in a tubular furnace and replaced with N2 at a flow rate of 200 mL / min for 30 min; under N2, the temperature is increased to 900°C at a heating rate of 20°C / min, and kept at this temperature for 2 h. After the temperature is lowered to room temperature, the first substrate after carbonization treatment is obtained.

[0165] (3) The carbonized first substrate obtained in step (2) was immersed in a 0.5 mol / L dilute nitric acid solution and treated at 60°C for 6 h. The solid phase was washed by filtration with deionized water for 3 times. The solid phase was then placed in a vacuum oven at 80°C and dried for 8 h to obtain a carbon carrier.

[0166] Comparative Example 2

[0167] This comparative example provides a catalyst, and the preparation steps are as follows:

[0168] (1) 2 g of spherical zinc oxide and 1 g of dopamine were dispersed and stirred in 300 mL of water, and then the pH of the system was adjusted to 8.5 with Tris-HCl buffer and stirred for 12 h; the solid phase was washed by filtration with deionized water for 3 times, and then the solid phase was placed in a vacuum oven at 80° C. and dried for 8 h to obtain a first matrix.

[0169] Among them, the D50 of spherical zinc oxide is 30nm.

[0170] (2) The first substrate prepared in step (1) is placed in a tubular furnace and replaced with N2 at a flow rate of 200 mL / min for 30 min; under N2, the temperature is increased to 900°C at a heating rate of 20°C / min, and kept at this temperature for 2 h. After the temperature is lowered to room temperature, the first substrate after carbonization treatment is obtained.

[0171] (3) The carbonized first substrate obtained in step (2) was immersed in a 0.5 mol / L dilute nitric acid solution and treated at 60°C for 6 h. The solid phase was washed by filtration with deionized water for 3 times. The solid phase was then placed in a vacuum oven at 80°C and dried for 8 h to obtain a carbon carrier.

[0172] (4) 0.10 g of the carbon carrier prepared in step (3), 0.50 g of the carbon carrier prepared in comparative example 1 and 1.06 g of chloroplatinic acid were ultrasonically mixed in 6 mL of water, and then the system after ultrasonic mixing was transferred to a glass surface dish, quickly pre-frozen in liquid nitrogen, and then transferred to a freeze dryer, cooled to -20 ° C at a freeze drying rate of 10 ° C / min, and then kept for 10 hours. Then the freeze-dried system was transferred to a porcelain boat and placed in a tube furnace, first replaced by N2 for 30 minutes, and then a mixed gas of H2 and N2 with a volume ratio of 0.075:1 was introduced, and the temperature was raised to 300 ° C at a heating rate of 20 ° C / min, and kept warm for 2 hours; then N2 was introduced for 1 hour, and then the temperature was reduced to room temperature to obtain a catalyst.

[0173] Experimental Example 1

[0174] The catalysts prepared in Examples 1 to 15 and Comparative Examples 1 to 2 were used to prepare membrane electrodes, and then polarization curve tests were performed on the membrane electrodes. The test results are as follows: Figure 2 and Figure 3And as shown in Table 1.

[0175] The steps of preparing a membrane electrode using a catalyst are as follows: taking 1 g of a catalyst (i.e., the catalyst prepared in Examples 1 to 15 or Comparative Examples 1 to 2), adding 50 mL of water, 150 mL of isopropanol, and a Nafion ionomer solution (purchased from DuPont, model: D520-1000EW) in sequence, and ultrasonically mixing for 2 h (wherein the mass ratio of the mass of the ionomer to the mass ratio of the carbon in the catalyst is 0.8) to prepare a slurry; spraying the above slurry on two opposite surfaces in the thickness direction of the proton membrane using an ultrasonic spraying instrument to form a cathode catalyst layer and an anode catalyst layer, respectively (wherein the Pt loading in the anode catalyst layer is 0.1 g / cm 2 The Pt loading in the cathode catalyst layer is 0.3 g / cm 2 ), and after drying, a catalyst coating membrane (CCM) is obtained; then, a frame and carbon paper are packaged on both sides of the CCM to obtain a membrane electrode.

[0176] The steps for the polarization curve test of the membrane electrode are as follows: hydrogen (0.6L / min) is distributed to the anode and air (1.1L / min) is distributed to the cathode, the relative humidity of the anode is set to 40%, the humidity of the cathode is set to 20%, the anode stack pressure is 160kPa, the cathode stack pressure is 180kPa, and the stack temperature is 80°C. Load to a current density of 3A / cm 2 The membrane electrode performance was tested after constant current activation for 30 min under hydrogen and oxygen conditions and then the cathode was switched to air and the voltage was stabilized for 20 min.

[0177] Table 1

[0178]

[0179]

[0180] Figure 2 The polarization curves of the membrane electrode prepared by using the catalysts prepared in Examples 1 to 3 of the present application are as follows: Figure 3 The polarization curve diagram of the membrane electrode prepared using the catalysts prepared in Example 1 and Comparative Examples 1-2 of the present application.

[0181] from Figure 2It can be seen that the particle size of spherical zinc oxide (i.e., spherical metal oxide) affects the MEA transport polarization. The spherical zinc oxide D50 (50 nm) in Example 2 is slightly larger than the spherical zinc oxide D50 (30 nm) in Example 1, and the spherical zinc oxide D50 (10 nm) in Example 3 is slightly smaller than the spherical zinc oxide D50 (30 nm) in Example 1, resulting in an increase in the MEA transport polarization of Examples 2 to 3 compared to the MEA transport polarization of Example 1.

[0182] from Figure 3 It can be seen that by comparing Example 1 with Comparative Examples 1 to 2, compared with the carbon carrier in Comparative Example 1 being a hollow rod-shaped carbon carrier and compared with the carbon carrier in Comparative Example 2 being a mixture of a hollow rod-shaped carbon carrier and a hollow spherical carbon carrier, the carbon carrier prepared in Example 1 can reduce the MEA transport polarization.

[0183] It can be seen from Table 1 that compared with the membrane electrodes prepared using the catalysts of Comparative Examples 1 to 2, the membrane electrodes prepared using the catalysts of Examples 1 to 15 have a higher current density of 1 A / cm 2 , 2A / cm 2 and 3A / cm 2 The voltage values ​​under are all higher, indicating that the catalysts of Examples 1 to 15 can reduce MEA transport polarization.

[0184] From the comparison of Examples 1 to 3, it can be seen that the particle size of the spherical metal oxide can further affect the transport polarization performance of MEA.

[0185] From the comparison between Example 1 and Examples 4 to 5, it can be seen that the aspect ratio of the rod-shaped metal oxide can further affect the transport polarization performance of MEA.

[0186] From the comparison between Example 1 and Examples 6 to 7, it can be seen that the mass ratio of the rod-shaped metal oxide to the carbon source coated on the outer surface of the rod-shaped metal oxide can further affect the transport polarization performance of the MEA.

[0187] From the comparison between Example 1 and Examples 8 to 12, it can be seen that the mass ratio of the first substrate to the spherical metal oxide can further affect the transport polarization performance of the MEA.

[0188] From the comparison between Example 1 and Examples 13 to 14, it can be seen that the mass ratio of the second substrate to the carbon source coated on the outer surface of the first substrate and the second substrate of the rod can further affect the transport polarization performance of the MEA.

[0189] In summary, the carbon carrier provided in the present application has a porous structure and a large specific surface area. When the carbon carrier is used to prepare a catalyst, the carbon carriers are not easy to agglomerate, so that the prepared catalyst has a higher porosity, and there are larger pores between the catalysts in the catalytic layer, which can increase the porosity of the catalytic layer in the membrane electrode, which is beneficial to improve the transmission of the reactants in the catalytic layer, reduce the mass transfer polarization loss of the catalytic layer, and reduce the mass transfer resistance of the catalytic layer, which is beneficial to improve the power generation performance of the membrane electrode under high current density.

[0190] The embodiments described above are part of the embodiments of the present application, rather than all of the embodiments. The detailed description of the embodiments of the present application is not intended to limit the scope of the present application for protection, but merely represents the selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present application.

Claims

1. A method for preparing a carbon carrier, characterized in that: include: Performing a first mixing of a first liquid phase containing a rod-shaped metal oxide and a first carbon source to allow the first carbon source to undergo a polymerization reaction, and drying the solid phase to obtain a first matrix; Then, a second liquid phase containing the spherical metal oxide and the first matrix is ​​subjected to a second mixing, and the solid phase is dried to obtain a second matrix; The third liquid phase containing the second carbon source and the second matrix is ​​then mixed for the third time to make the second carbon source undergo a polymerization reaction, and the third matrix is ​​obtained after the solid phase is dried; the third matrix is ​​carbonized, and then the carbonized third matrix is ​​mixed for the fourth time with an acid solution, so that the acid solution can remove the rod-shaped metal oxide and the spherical metal oxide in the third matrix; The first carbon source and the second carbon source each independently include at least one of dopamine, pyrrole and aniline; The carbon carrier comprises: a carbon tube and a carbon ball connected to the outer surface of the carbon tube; The carbon sphere is a hollow structure, and both the carbon tube and the carbon sphere are non-closed structures.

2. The method for preparing a carbon carrier according to claim 1, characterized in that: The diameter of the rod-shaped metal oxide is 20nm-240nm, and the length of the rod-shaped metal oxide is 50nm-500nm.

3. The method for preparing a carbon carrier according to claim 1, characterized in that: The aspect ratio of the rod-shaped metal oxide is 2.25-11.

25.

4. The method for preparing a carbon carrier according to claim 1, characterized in that The mass ratio of the first carbon source to the rod-shaped metal oxide is 1:(5-20).

5. The method for preparing a carbon carrier according to claim 1, characterized in that: The particle size of the spherical metal oxide is 10nm~50nm.

6. The method for preparing a carbon carrier according to claim 1, characterized in that: The mass ratio of the spherical metal oxide to the first matrix is ​​1:(1-10).

7. The method for preparing a carbon carrier according to claim 1, characterized in that: The material of the spherical metal oxide and the rod-shaped metal oxide each independently includes at least one of zinc oxide, copper oxide and magnesium oxide.

8. The method for preparing a carbon carrier according to claim 1, characterized in that The mass ratio of the second carbon source to the second matrix is ​​1:(0.25-4).

9. The method for preparing a carbon carrier according to claim 1, characterized in that: The carbonization treatment is performed under an inert atmosphere, and the temperature of the carbonization treatment is 800° C. to 1200° C.

10. A catalyst, characterized in that include: A carbon carrier and a catalytic material supported on the surface of the carbon carrier; Wherein, the carbon carrier is a carbon carrier prepared by the method for preparing a carbon carrier according to any one of claims 1 to 9.

11. The catalyst according to claim 10, characterized in that The length of the carbon tube is 60nm-540nm, the outer diameter of the carbon tube is 30nm-280nm, and the thickness of the carbon tube is 5nm-20nm.

12. The catalyst according to claim 11, characterized in that The aspect ratio of the carbon tube is 2-12.

13. The catalyst according to claim 11, characterized in that The particle size of the carbon sphere is 15nm~60nm, and the thickness of the carbon sphere is 5nm~20nm.

14. The catalyst according to any one of claims 10 to 13, characterized in that The tube wall of the carbon tube and the spherical shell of the carbon sphere are both porous structures.

15. The catalyst according to claim 10, characterized in that The catalytic material includes at least one of a single substance of Pt and a Pt alloy.

16. A membrane electrode, characterized in that: The catalyst layer of the membrane electrode contains the catalyst according to any one of claims 10 to 15.

Citation Information

Patent Citations

  • Sulfur / carbon composite material and preparation method and application thereof

    CN111661835A